2020
DOI: 10.1111/jdv.16272
|View full text |Cite
|
Sign up to set email alerts
|

Incompletely excised lentigo maligna melanoma is associated with unpredictable residual disease: clinical features and the emerging role of reflectance confocal microscopy

Abstract: Background Lentigo maligna/lentigo maligna melanoma (LM/LMM) poses a treatment and surgical challenge given unpredictable subclinical extension resulting in incomplete excision. Objectives To describe the demographic, clinical and pathologic characteristics of incompletely excised LM/LMM. To evaluate the potential role of reflectance confocal microscopy (RCM). Patients and methods A retrospective review of a melanoma database at a tertiary cancer centre for patients referred with 'incompletely excised LM/LMM' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Complex cases are more likely to be referred to a specialist Melanoma Unit, including patients with large lesions, those involving cosmetically or functionally difficult sites, or a recurrence. Therefore, our observed 38% recurrence rate over a median of 7.5 years is likely to be biased upwards to a substantial degree when compared to LM/LMM patients treated in the community 13,33 . On the other hand, the median of the long axis size of LM/LMM in our series (14 mm) was similar to a cohort study conducted in the United Kingdom, which included all patients with a LM diagnosis at the central pathology department in Leicestershire, irrespective of the referral clinic: Osborne et al reported a LM mean size of 14.4 mm with a recurrence rate of 20% at a mean follow‐up of 42 months in completely excised lesions, 35 similar to our finding of 24% recurrence rate after surgery with clear margins.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Complex cases are more likely to be referred to a specialist Melanoma Unit, including patients with large lesions, those involving cosmetically or functionally difficult sites, or a recurrence. Therefore, our observed 38% recurrence rate over a median of 7.5 years is likely to be biased upwards to a substantial degree when compared to LM/LMM patients treated in the community 13,33 . On the other hand, the median of the long axis size of LM/LMM in our series (14 mm) was similar to a cohort study conducted in the United Kingdom, which included all patients with a LM diagnosis at the central pathology department in Leicestershire, irrespective of the referral clinic: Osborne et al reported a LM mean size of 14.4 mm with a recurrence rate of 20% at a mean follow‐up of 42 months in completely excised lesions, 35 similar to our finding of 24% recurrence rate after surgery with clear margins.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, our observed 38% recurrence rate over a median of 7.5 years is likely to be biased upwards to a substantial degree when compared to LM/LMM patients treated in the community. 13,33 On the other hand, the median of the long axis size of LM/LMM in our series (14 mm) was similar to a cohort study conducted in the United Kingdom, which included all patients with a LM diagnosis at the central pathology department in Leicestershire, irrespective of the referral clinic: Osborne et al reported a LM mean size of 14.4 mm with a recurrence rate of 20% at a mean follow-up of 42 months in completely excised lesions, 35 similar to our finding of 24% recurrence rate after surgery with clear margins. Moreover, one important distinction between our study and those previously published is that most prior studies had less than 5-year follow-up 19,20,35 ; thus, recurrence rates in the literature may be grossly underestimated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations